ISOLATED OVARIAN TUBERCULOSIS MIMICKING OVARIAN CARCINOMA: CASE REPORT AND LITERATURE REVIEW - Rabesalama, Solohery Solofomandimby Edison Nirina; Mandeville, Kate Louise; Raherison, Romain Aristide; Rakoto-Ratsimba, Hery Nirina (African Journal of Infectious Diseases (AJID), 2010)
Although genitourinary tuberculosis is common, reports of isolated ovarian tuberculosis are rare. However, its presentation can mimick that of an ovarian tumour, leading to diagnostic difficulties. A woman of 17 years presented with chronic pelvic pain, weight loss, a right ovarian mass on ultrasound, and a significantly elevated CA-125 level. A diagnosis of ovarian carcinoma was made, and laparotomy was performed with resection of the right ovary. Postoperative histological examination, however, revealed classic tuberculoid appearances, with no signs of malignancy. Antituberculosis treatment was commenced, with full resolution of her symptoms and a decrease in CA-125 level. Isolated ovarian tuberculosis is most common in young women living in endemic zones. CA-125 can be raised in both conditions, and imaging is rarely conclusive. Intraoperative frozen section of tissue specimens can be helpful if available. Early diagnosis of ovarian tuberculosis is vital as untreated disease can lead to infertility.